Saccades during visual exploration align hippocampal 3–8 Hz rhythms in human and non-human primates - Hoffman, Kari L.; Dragan, Michelle C.; Leonard, Tim K.; Micheli, Cristiano; Montefusco-Siegmund, Rodrigo; Valiante, Taufik A. (Frontiers in Systems Neuroscience, 2013)
Visual exploration in primates depends on saccadic eye movements that cause alternations of neural suppression and enhancement. This modulation extends beyond retinotopic areas, and is thought to facilitate perception; yet saccades may also influence brain regions critical for forming memories of these exploratory episodes. The hippocampus, for example, shows oscillatory activity that is generally associated with encoding of information. Whether or how hippocampal oscillations are influenced by eye movements is unknown. We recorded the neural activity in the human and macaque hippocampus during visual scene search. Across species, saccadic eye movements were associated with a time-limited alignment of a low-frequency (3-8 Hz) rhythm. The phase alignment depended on the task and not only on eye movements per se, and the frequency band was not a direct consequence of saccade rate. Hippocampal theta-frequency oscillations are produced by other mammals during repetitive exploratory behaviors, including whisking, sniffing, echolocation and locomotion. The present results may reflect a similar yet distinct primate homologue supporting active perception during exploration.